2016
DOI: 10.1093/molbev/msw045
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Impact of Chromosomal Inversions on Gene Expression Uncovers Robustness via Phenotypic Buffering

Abstract: The nonrandom gene organization in eukaryotes plays a significant role in genome evolution and function. Chromosomal structural changes impact meiotic fitness and, in several organisms, are associated with speciation and rapid adaptation to different environments. Small sized chromosomal inversions, encompassing few genes, are pervasive in Saccharomyces “sensu stricto” species, while larger inversions are less common in yeasts compared with higher eukaryotes. To explore the effect of gene order on phenotype, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 126 publications
(153 reference statements)
3
40
0
Order By: Relevance
“…Although inversions can be engineered for proof of function in some organisms 30 , this is infeasible in Boechera . However, the KB model predicts that relatives of the ancestral haplotype that gave rise to the inversion might still exist as non-inverted genotypes nearby.…”
Section: Qtls Within the Inversionmentioning
confidence: 99%
“…Although inversions can be engineered for proof of function in some organisms 30 , this is infeasible in Boechera . However, the KB model predicts that relatives of the ancestral haplotype that gave rise to the inversion might still exist as non-inverted genotypes nearby.…”
Section: Qtls Within the Inversionmentioning
confidence: 99%
“…Identification of this translocation required reads to span at least 12 Kbp due to the large repetitive elements surrounding the translocation breakpoints, explaining why it was previously undetected. While the translocation did not disrupt any coding sequence and is unlikely to cause phenotypical changes (Naseeb et al 2016), there may be decreased spore viability upon mating with other CEN.PK strains. Our ability to detect structural heterogeneity within a culture shows that nanopore sequencing could also be valuable in detecting structural variation within a genome between different chromosome copies, which occurs frequently in aneuploid yeast genomes (Gorter de Vries, Pronk and Daran 2017).…”
Section: Discussionmentioning
confidence: 89%
“…It has been shown that S. cerevisiae strains carrying single gene inversions can cause fitness defects in nutrient‐limited media (Naseeb & Delneri, ). However, large chromosomal inversions in S. cerevisiae can be either lethal or neutral depending upon the environmental conditions (Naseeb et al, ). Similar findings were observed by Avelar et al () in S. pombe , showing that inversions and translocations can have beneficial or deleterious growth affects for both meiotic and mitotic fitness.…”
Section: Cre‐loxp Mediated Recombinationmentioning
confidence: 99%
“…Therefore, by the action of the Cre recombinase, the selectable marker can be rescued, leaving only one loxP 'scar' in the genome. The key benefit of this system is that the Cre recombinase can catalyse either multiple gene deletions (Akada et al, 2006), inversions (Naseeb et al, 2016;Naseeb & Delneri, 2012) or translocations of a chromosomal fragment (Delneri et al, 2003) depending on the orientation and location of loxP sequences flanking that fragment. When multiple deletions is the objective of the study, the availability of multiple different loxP sequences (Carter & Delneri, 2010) Overview of the yeast genome editing methods described here.…”
Section: Cre-loxp Mediated Recombinationmentioning
confidence: 99%
See 1 more Smart Citation